Mergeable nervous systems for robots - Nithin Mathews (Nature Portfolio, 2017)
Robots that can self-assemble into different morphologies are desired to perform tasks that require different physical capabilities. Mathews et al. design robots whose bodies and control systems can merge and split to form new robots that retain full sensorimotor control and act as a single entity.